Gestión deportiva: un débil camino hacia el deporte de alto rendimiento - Tello De La Cruz, José Carlos (2021)
Within the government agenda, the sport has not had relevant participation despite the multiple benefits it has on society. However, with the passage of time and the effort of different actors and institutions, this is gradually being inserted into the programming of State projects. Sports management not only involves administration issues within sports entities; rather, like management itself, it covers issues outside the organization; and, it should be noted, that sport is usually divided into 3 parts: the recreational practice of sport, sports masses, and high performance sports. That is why it is necessary to obtain a holistic and comprehensive vision of the path that the athlete has to be able to develop towards any of these aforementioned divisions.